2013
DOI: 10.1186/1745-6215-14-229
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effect of low-level laser therapy on adolescents with temporomandibular disorder: study protocol for a randomized controlled trial

Abstract: BackgroundA number of problems involving the temporomandibular joint (TMJ) and associated structures can lead to temporomandibular disorder (TMD). The aim of the proposed study is to assess the effect of low-level laser therapy on occlusal contacts, mandibular movements, electromyography activity in the muscles of mastication and pain in adolescents with TMD.Methods/DesignA randomized, controlled, double-blind, clinical trial will be carried out involving 85 male and female adolescents between 15 and 18 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 18 publications
0
25
0
7
Order By: Relevance
“…As três avaliações foram realizadas por um cirurgião-dentista e contemplavam anamnese, exame clínico com mensuração da AMM (aplicação dos eixos I e II dos RDC) e aplicação da escala visual analógica de dor (EVA), bem como a aplicação do questionário de qualidade de vida Medical Outcomes Study 36-item Short Form Health Survey (SF-36) antes e após o tratamento. Nas três avaliações foram seguidas as diretrizes da Associação Internacional de Pesquisa Odontológica, que recomendam uma única medida para cada movimento [6,9], também com base nos RDC para DTM.…”
Section: Avaliaçõesunclassified
See 1 more Smart Citation
“…As três avaliações foram realizadas por um cirurgião-dentista e contemplavam anamnese, exame clínico com mensuração da AMM (aplicação dos eixos I e II dos RDC) e aplicação da escala visual analógica de dor (EVA), bem como a aplicação do questionário de qualidade de vida Medical Outcomes Study 36-item Short Form Health Survey (SF-36) antes e após o tratamento. Nas três avaliações foram seguidas as diretrizes da Associação Internacional de Pesquisa Odontológica, que recomendam uma única medida para cada movimento [6,9], também com base nos RDC para DTM.…”
Section: Avaliaçõesunclassified
“…A irradiação foi feita de forma pontual, em contato e perpendicularmente, sobre quatro pontos em forma de cruz na região pré-auricular (Figura 1A), um ponto no meato acústico externo [5][6][7]20] (Figura 1B), seis pontos nos músculos masseter (Figura 1C), e dois pontos no músculo temporal (feixe anterior) [2,5,9,20].…”
Section: Protocolo De Tratamentounclassified
“…Kötü postür, parafonksiyonel alışkanlıklar, maloklüzyon ve psikososyal faktörler TMR'ın gelişiminde başlıca etkenlerdir. TMR'ın kompleks etiyolojisine bağlı olarak akupunktur, masaj, ultrason, ilaç tedavisi, psikolojik tedavi, ısırma plakları ve DSLT gibi farklı tedavi seçenekleri önerilmektedir (30). TMR'ın tedavisinde başlıca amaç ağrıyı azaltmak ve çene hareketlerinin sınırlarını genişletmektir.…”
Section: Discussionunclassified
“…LLL induces mitochondrial activity and tissue regeneration by increasing cell turnover, selective absorption, nerve injury repair, angiogenesis, controlling inflammation, vasodilation, release of endogenous endorphins, increasing the oxygen supply, and changing the permeability of tissues. (6)(7)(8)(9)(10)(11)(12)(13)(14) Although the exact mechanism of analgesia by laser has yet to be fully understood, some in-vitro studies have shown that LLLT inhibits the cyclooxygenase 2 synthesis and prevents the conversion of arachidonic acid to prostaglandins E2 and F2 and thromboxane, resulting in analgesia. (15) Some clinical studies have con-cluded that increased level of beta-endorphin in the central nervous system and the consequently increased pain threshold are the main mechanisms of analgesia by laser application.…”
Section: Introductionmentioning
confidence: 99%